Retrospective Analysis Of Blood Donor Deferral Pattern In A Tertiary Care Hospital In Puducherry (Journal of Namibian Studies : History Politics Culture, 2024)
Blood donation is a vital part of worldwide healthcare. Voluntary donors, many times have been deferred due to numerous reasons, temporarily or permanently. The reasons for deferral vary in different regions. Knowledge of the relative prevalence and identification of pattern and trend in donor deferral can be used as tools for developing policies and taking further initiatives in donor education and encouragement Aim: To determine the prevalence of deferral and assess the pattern of donor deferrals with regard to age, sex, type and cause of deferral. Materials and Methods: This retrospective cross sectional study was conducted in Blood bank, Department of Pathology, Sri Venkateshwaraa Medical College And Research Centre using data of all donor deferrals which has been reported from January 2018 to April 2022. Results: Total no of donors deferred in our study was 300. Among them 261 were Male and 39 were female. The mean years of age of the deferral group were 28.7 +/- 8.46. There were about 267 (89%) deferred due to temporary reasons and 33 (11%) deferred due to permanent reasons. In the temporary deferral group the most common cause for deferral was found to be  anemia (29%) followed by tattoo (20%) and Alcohol intake(14%).Out of the 33 permanent deferrals 14 were deferred due to diabetes, 7 due to asthma and 6 each were deferred  due to hypertension and medication. Conclusion: It is necessary that every blood bank  analyze the  health status, rates and patterns of donor deferral in their own region, so that unnecessary deferral especially due to temporary reasons can be avoided by conducting awareness programmes and  mass screening programs before blood donation camps can be organized.